Campus Concrete - McCarthy, Christine (Architectural History Aotearoa, 2022)
This paper will look at the celebrations of concrete apparent in the Brutalist architecture of the 1970s. It will particularly examine Toomath's Wellington Teachers' Training College (Stage I design 1962-65, built 1966-69; Stage II design 1966-69; built 1972-75), Chris Brooke-White's Central Institute of Technology campus in Heretaunga, Upper Hutt (Stage 1, 1969-72; Stage II, 1972-77), and Ted McCoy's additions to Otago University (namely the Archway Theatres (1972-73) and the Hocken Building (1979-80)). Concrete is understood on these sites as textures as well as spatial articulators. Helmut Einhorn's 1975 consideration of concrete surfaces for the Wellington Urban Motorway, Charles Fearnley's 1975 Where have all the Textures gone? and Banham's 1955 "The New Brutalism," will provide the prime theoretical context.